Climate change adaptation, gender, and mainstreaming: The role of gender in Fiji's relocation initiative - Bertana, Amanda; Blanton, Natalie (Climate and Development, 2022)
Climate change has elucidated already existing gender inequalities associated with unequal access to resources, decision-making processes, and higher exposure to environmental shocks and stressors. Growing acknowledgment of the gender-differentiated implications of climate change in recent years has placed gender equality as a focal point in international discourses on climate change adaptation. The policy perspective of gender equality is universalized, but how it transcribes in local climate change adaptation projects remains elusive. Using the relocation of Vunidogoloa, Fiji, this article explores the tension and compatibility between the way gender equality is discussed and how it is implemented in climate change adaptation projects. © 2022 Informa UK Limited, trading as Taylor & Francis Group.
Keywords: 2000 à aujourd'hui; 2010-2019; changements climatiques; discipline; environnement; ethnographie; fidji; océanie; projet charge mentale; périodes historiques; ressource en ligne; régions géographiques; santé; sciences humaines; sociologie; sécurité alimentaire; thématiques

"I’m strong within myself": Gender, class and emotional capital in childcare - Andrew, Yarrow (British Journal of Sociology of Education, 2015)
Emotions have received increasing attention in educational circles in the last decade. Drawing on Bourdieu, feminist scholars use emotional capital to illustrate the ways gendered inequalities can compound the disadvantages of social class. This paper examines relationships within childcare services in Australia, showing how emotional capital functions as a resource for staff. Data from interviews with childcare staff illustrate key aspects of emotional capital, such as reflexivity, resilience and embodiment. Findings show that investing in emotional capital is the key to a long-lasting commitment to childcare work, and should be valued accordingly. © 2013 Taylor & Francis.
Keywords: 2000 à aujourd'hui; 2010-2019; australie; capital émotionnel; care; discipline; maternité; océanie; projet charge mentale; périodes historiques; ressource en ligne; régions géographiques; sciences humaines; service de garde; sociologie; thématiques; travail; travail du care